Osteoprogenitor cells of mature human skeletal muscle tissue: an in vitro study. - Levy, M; Joyner, C; Virdi, A; Reed, A; Triffitt, J; Simpson, A; Kenwright, J; Stein, H; Francis, M (2001)
The presence of osteogenic progenitors in human skeletal muscle is suggested by the formation of ectopic bone in clinical and experimental conditions, but their direct identification has not yet been demonstrated. The aims of this study were to identify osteogenic progenitor cells in human skeletal muscle tissue and to expand and characterize them in culture. Specimens of gracilis and semitendinosus muscle were obtained from young adults and digested to separate the connective tissue and satellite cell fractions. The cells were cultured and characterized morphologically and immunohistochemically using antibodies known to be reactive with primitive osteoprogenitor cells, pericytes, intermediate filaments, and endothelial cells. Alkaline phosphatase activity and osteocalcin gene expression were also determined. In the early stages of culture, the connective tissue cells obtained were highly positive for primitive osteoprogenitor cell and for pericyte markers. Alkaline phosphatase activity was detectable at early stages of culture and rose as a function of time, whereas primitive osteoprogenitor cell markers declined and osteocalcin mRNA expression became detectable by reverse transcriptase-polymerase chain reaction (RT-PCR). It is shown that human skeletal muscle connective tissue contains osteogenic progenitor cells. Their identification as pericytes, perivascular cells with established osteogenic potential, suggests a cellular link between angiogenesis and bone formation in muscle tissue. These cells are easily cultured and expanded in vitro by standard techniques, providing an alternative source of osteogenic progenitor cells for possible cell-based therapeutic use in certain conditions.